Impact oriented monitoring: A new methodology for monitoring and evaluation of international public health research projects (2015)
Impact oriented monitoring (IOM) is a novel methodology for identifying and assessing the impacts of EU-funded research projects in the area of International Public Health. A framework based on the logic and payback categories is used to categorize, into multi-dimensions, the impacts produced by public health research projects. A set of tools, including: 1) a project results framework; 2) a coordinators' survey; 3) an end users' survey, and 4) an assessment tool (scoring matrix), have been developed for both collecting data on results and activities and helping in assessing impacts. The need to know the impact of the projects based on robust data but, at the same time, to minimize the time and resources required of both the EC officers implementing the methodology and the project coordinators providing data on results and impacts, has led to the development of the IOM methodology. The methodology is expected to provide the DG Research and Innovation of the European Commission (EC) with usable information on how the research projects in the area of international public health are producing impacts. More importantly, this information could improve the performance of existing programmes and also form the basis for supporting research policy planning. The IOM methodology can be easily adapted to other ECfunded research areas and also implemented in other countries by institutions responsible for funding research activities. © The Author 2015.